Analysis Of The Effectiveness Of Social Protection Networks In Syria During The Period 2000-2016 - رجب, هدى (Latakia University Journal - Economic and Legal Sciences Series, 2020)
Global attention to protection nets has increased, especially after the global economic crisis (2008-2011), which highlighted the importance of good social protection nets in reducing poverty and addressing vulnerabilities, especially in low-income and crisis countries. It is known that The terrorist war that has afflicted Syria since the beginning of 2011 has brought the country into a state of political and economic instability which has resulted in deterioration in the productive structures, high unemployment and inflation, low purchasing power of the Syrian pound, an increase in poverty rates and almost complete absence of the middle class in Syria. Therefore, the need for social protection and its tools to mitigate the negative effects of the war on the citizens has increased. This research sheds light on the reality of protection networks in Syria during the period 2000-2016 , with a focus on the period of the war to analyze its effectiveness and identify its strengths and weaknesses in the hope of activating its role in the reconstruction phase in Syria.